Race development in men`s 400 m track and field events - Yoshimoto, T.; Chiba, Y.; Sato, K.; Takai, Y. (Scientific Journal of Sport and Performance, 2025)
This study aimed to clarify race development in men`s 400 m track and field events. We analyzed 457 races involving 155 male long sprinters, including 400 m race records and each 50 m split time. The races were categorized into seven groups based on 400 m race times: 43.0-second (n = 6), 44.0-second (n = 21), 44.5-second (n = 25), 45.0-second (n = 21), 45.5-second (n = 26), 46.0-second (n = 33), and 47.0-second (n = 23). The percentage of each 50 m split time relative to the 400 m race time (%ST) was calculated. Running speeds in all sections were higher in races with faster 400 m times. The %ST in the 0-50 m section was significantly greater in 43.0- and 44.5-second groups than in the 46- and 47-second groups. The %ST in the 0-50 m section showed a negative correlation with the 400 m race time, whereas %ST in the 100-150 m, 150-200 m, and 250-300 m sections exhibited positive correlations. These findings show that faster races were characterized by relatively lower running speeds in the first 50 m and higher speeds in the second 200 m, suggesting strategic race development in faster long sprinters.